Achieving tuberculosis elimination in Canada and the USA: giving equal weight to domestic and international efforts - Namrata Rana; James C. Johnston; Kevin Schwartzman; Olivia Oxlade; Pedro G. Suarez; Michel Gasana; Megan Murray; Grania Brigden; Jonathon R. Campbell (BMC Global and Public Health, 2024)
Abstract A major contributor to the tuberculosis burden in the United States (US) and Canada is the progression of tuberculosis infection acquired before immigration among persons born outside the US and Canada. Domestic interventions against tuberculosis, such as those associated with tuberculosis infection testing and treatment, while critical, are alone insufficient to address tuberculosis and achieve elimination. To hasten tuberculosis elimination in North America, coupling domestic efforts with consistent funding and multifaceted support for tuberculosis detection, treatment, and prevention worldwide is necessary. These efforts will reduce tuberculosis transmission and the prevalence of tuberculosis infection in an increasingly globalized world. We discuss the epidemiologic and economic rationale for this approach, as well as current efforts and potential strategies. We further place in context benchmark tuberculosis programs that have used international funding to achieve a sustained decline in tuberculosis incidence, as exemplars for the importance of such funding to international progress towards elimination. We conclude by providing suggestions for future pathways toward sustainable programs. Following the substantial global and local response to COVID-19, we call for the same intensity to eliminate this millennia-old disease.